The Global Burden of Lead Toxicity Attributable to Informal Used Lead-Acid Battery Sites - Bret Ericson; Phillip Landrigan; Mark Patrick Taylor; Joseph Frostad; Jack Caravanos (Ubiquity Press, 2017)
Background Prior calculations of the burden of disease from environmental lead exposure in low- and middle-income countries (LMICs) have not included estimates of the burden from lead-contaminated sites because of a lack of exposure data, resulting in an underestimation of a serious public health problem. Objective We used publicly available statistics and detailed site assessment data to model the number of informal used lead-acid battery (ULAB) recyclers and the resulting exposures in 90 LMICs. We estimated blood lead levels (BLLs) using the US Environment Protection Agency's Integrated Exposure Uptake Biokinetic Model for Lead in Children and Adult Lead Model. Finally, we used data and algorithms generated by the World Health Organization to calculate the number of attributable disability adjusted life years (DALYs). Results We estimated that there are 10,599 to 29,241 informal ULAB processing sites where human health is at risk in the 90 countries we reviewed. We further estimated that 6 to 16.8 million people are exposed at these sites and calculate a geometric mean BLL for exposed children (0-4 years of age) of 31.15 μg/dL and a geometric mean BLL for adults of 21.2 μg/dL. We calculated that these exposures resulted in 127,248 to 1,612,476 DALYs in 2013. Conclusions Informal ULAB processing is currently causing widespread lead poisoning in LMICs. There is an urgent need to identify and mitigate exposures at existing sites and to develop appropriate policy responses to minimize the creation of new sites.